AB0135 Decreased Lupus Manifestations in Pristane-Induced Microrna 155-Deficient Mice. (15th July 2016) - Leiss, H.; Salzberger, W.; Jacobs, B.; Gessl, I.; Kozakowski, N.; Blüml, S.; Puchner, A.; Niederreiter, B.; Shvets, T.; Steiner, C.W.; Smolen, J.; Stummvoll, G.
Abstract : Background: Deregulation of endogenous miR155 was observed in many autoimmune conditions, including systemic lupus erythematosus (SLE). Objectives: We herein examined the role of miR155 in the development of systemic manifestations in mice with pristane-induced lupus (PIL). Methods: MiR155-deficient and C57/Bl6 mice were injected with pristane or PBS as control and analyzed after 8 months. Glomerulonephritis and pneumonitis were quantified by using the composite kidney biopsy score (KBS) and by analyzing the numbers of affected lung-vessels and the area of the inflammatory lung-infiltrate, respectively. Specimens were stained with B220 (B), CD3 (T), Neu7/4 (neutrophils) and F4/80 (macrophages) and analyzed by cell-identification algorithms for nuclear segmentation (HistoQuest). Serum levels of anti-dsDNA, anti-histone and anti-chromatin antibodies were measured by ELISA. Frequencies of B cells, activated and regulatory CD4+ T cells as well as Th1, Th2, Th17 cells were measured by flow cytometry. Quantitative real-time polymerase chain reaction was used to measure expression levels of interferon-signature and T-cell subset related as well as miR155-associated genes. Results: All pristane-injected mice showed signs of pneumonitis, while controls did not. Compared to wild types treated with pristane, similarly treated knockouts showed significantly decreased perivascular inflammatory area with B cells being the most prominent inflammatory cell. Wildtypes had a more severe renal involvement in the KBS than knockouts. Corresponding with reduced organ involvement, miR155 deficient mice had significantly lower serum levels of anti-dsDNA antibodies, anti-chromatin and anti-histone antibodies and decreased frequencies of activated CD4 + CD25 + (Foxp3 – ) cells. Interestingly, also frequencies of CD4 + CD25 + Foxp3 + regulatory T cells were lower in these mice. Upon restimulation, CD4 + cells showed a more pronounced Th2 response in wild types, but no significant differences in Th1 and Th17 phenotype. Regarding INF-signature and T-cell subset activation, pristane-treated wild types showed significantly up-regulated gene-expression patterns whereas equivalently treated mutants showed the same levels as PBS-treated controls. Conclusions: MiR155 deficiency in PIL mice did not prevent disease, but was associated with less severe organ involvement, lower serum auto-abs levels, lower frequencies of Th2 cells, whereas lower expressions of genes jointly responsible for disease development may be one key mechanism. Thus, antagonisation of miR155 might be a future approach in treating SLE. Disclosure of Interest: None declared